Analysis of Cuttings Transport in Small‐Bore Horizontal Wells Considering Drill String Eccentricity - An Jintao; Li Jun; Honglin Huang; Hui Zhang; Hongwei Yang; Geng Zhang; Sainan Chen; Qiuxia Lai (Energy Science & Engineering)
ABSTRACT The narrow annulus in small‐bore horizontal wells causes marked differences in cuttings transport compared to conventional horizontal wells. To address this issue, a CFD‐based numerical model for solid‐liquid two‐phase flow in the annulus was developed, accounting for the eccentricity of the drill string. The study examines the effects of key factors, including flow rate, drill pipe rotation speed, well inclination angle, and drilling fluid properties, on cuttings transport in small‐bore horizontal wells. Results show that increasing drill pipe rotation speed enhances tangential and axial velocities of the annular fluid by up to 25%, expanding the “viscous coupling” region. This facilitates the upward movement of cuttings from the lower to the upper side of the annulus, improving cuttings transport. Increasing drilling fluid density enhances cuttings buoyancy, reducing their deposition by 43%. A “critical rotation speed” and “critical flow rate” exist, below which cuttings transport is most difficult in highly inclined sections and above which transport is most challenging in horizontal sections. Increasing drilling fluid density enhances cuttings buoyancy, reducing their deposition. The effect of rheological parameters on hole cleaning efficiency exhibits a nonlinear trend, with an optimal range of these parameters existing under varying flow rates and drill pipe rotation speeds. These findings offer guidance for optimizing hydraulic parameters in small‐bore horizontal wells and preventing stuck pipe incidents.